The Emerging Roles of Histology in the Management of Lung Cancer - Naif Alsuhaymi (Pakistan Journal of Medical & Health Sciences, 2022)
For many years, non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) have been treated as single-disease entities. However, there are significant histologic and molecular differences between the various types of lung cancers. Such differences influence the various chemotherapeutic agents’ outcomes and side effect profiles. For instance, bevacizumab causes significant pulmonary hemorrhage in squamous cell carcinoma; hence it is not recommended to treat such histologic subtypes. SCLC is more aggressive than NSCLC; therefore, it demonstrates differences in tumor behavior and the need to approach treatments differently. To date, studies of various lung cancers have provided new insight into their molecular characteristics. The histological classification does not only focus on the morphology but can provide detailed histological characteristics that will promote targeted therapy. Can this new knowledge assist in developing more effective drugs for lung cancers? In this paper, the review shows the advancements in histological diagnosis of lung cancers and their use in the optimal treatment of lung cancers. Keywords: Small cell lung cancer, non-small cell lung cancer, histological subtypes.